The effects of different velogenic NDV infections on the chicken bursa of Fabricius - Teo, Kristeen Ye Wen (BioMed Central, 2017)
Background: Virulent Newcastle disease virus (NDV) was reported to cause rapid depletion of chicken bursa of Fabricius. Severe pathological condition of the organ is commonly associated with high levels of virus replication, intense inflammatory response and also the degree of apoptosis. In this study, the responses of chicken bursa of Fabricius infected with two different strains of velogenic NDV, namely AF2240 and IBS002, were investigated by observing cell population changes, oxidative stress, viral replication and cytokine expression in the organ. Subsequently, apoptosis of enriched bursal IgM+ cells was determined to help us elucidate possible host pathogen relationships between the chicken bursa of Fabricius and NDV infection. Results: The depletion of IgM+ cells and infiltration of macrophages were observed to be higher in bursa infected with AF2240 as compared to IBS002. In line with the increment of the macrophage population, higher nitric oxide (NO) and malondialdehyde (MDA) contents which indicated higher oxidative stress were also detected in bursa infected with NDV AF2240. In addition, higher pro-inflammatory cytokines and chemokine gene expression such as chicken CXCLi2, IL-18 and IFN-γ were observed in AF2240 infected bursa. Depletion of IgM+ cells was further confirmed with increased cell death and apoptosis of the cells in AF2240 infected bursa as compared to IBS002. However, it was found that the viral load for NDV strain IBS002 was comparatively higher than AF2240 although the magnitude of the pro- inflammatory cytokines expression and cell apoptosis was lower than AF2240. Conclusion: The results of our study demonstrated that infection of NDV strains AF2240 and IBS002 caused apoptosis in bursa IgM+ cells and its severity was associated with increased expression of pro-inflammatory cytokines/chemokine, macrophage infiltration and oxidative stress as the infection duration was prolonged. However, of the two viruses, we observed that NDV AF2240 induced a greater magnitude of apoptosis in chicken bursa IgM+ cells in comparison to IBS002. This might be due to the high level of oxidative stress and inflammatory cytokines/chemokine as well as lower IL10 expression which subsequently led to a high rate of apoptosis in the chicken bursa of Fabricius although the detected viral load of AF2240 was lower than IBS002.